PENERAPAN PSAP NO. 01 DALAM PERTANGGUNGJAWABAN KEUANGAN DI DESA PENTADIO TIMUR - Noho, Maryam; Ali, Yuwin (Program Studi Akuntansi, 2021)
This study aims to determine the application of the Governmental Accounting Standard Statement (PSAP) No. 01 In Village Financial Accountability in Pentadio Timur Village, Telaga Biru District, Gorontalo District. This type of research uses descriptive research with a qualitative approach by Nazir (2009). The results of this study are that the financial accountability reporting in Pentadio Timur Village, Telaga Biru District, Gorontalo Regency is in accordance with the Minister of Home Affairs Regulation Number 20 of 2018 in the fifth part of article 70 regarding Village financial accountability and is based on the Government Accounting Standards Statement (PSAP) No. 01. However, it is not yet fully in accordance with the implementing regulations. Where the Village Government has only made four of the seven rules of financial accountability reports, while in the regulation on Implementation of PSAP No. 01 it has 7 (tuju) components of the rules. In this case, it is hoped that the Government will make a village financial accountability report in accordance with Government Regulation Number 71 of 2010 based on PSAP No. 01 by completing the components of financial statements in order to create accountable and transparent financial reports